Выражение 9x^3-(3x-x)(3x+1) и вычислите его значение при х=94

sempai1 sempai1    2   29.07.2019 09:50    1

Ответы
Ivan208280 Ivan208280  03.10.2020 16:27
Заданное выражение:
9х³ - (3х -х)(3х+1) =
= 9х³ - 2х(3х+1) =
= 9х³ - 6х² - 2х =
= х *(9х² - 6х - 2) =
= x * ( 3x(3x-2) - 2)
при х = 94 
94 *(3*94*(3*94-2) -2 ) =  94 * ( 282 *(282 - 2)  - 2) = 
= 94 * (282 * 280 - 2) = 94 * 78958 = 7422052
ответ : 7422052

Выражение с учетом комментария :
9x³ - (3x² - x)(3x+1) =
= 9x³ -  (3х² * 3х + 3х² *1  - х*3х  -х*1) =
= 9х³  - (9х³  + 3х² - 3х²  - х) =
= 9х³ - (9х³ - х) =
= 9х³  - 9х³  + х = 
= х
при х = 94  ⇒ ответ :  94.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра